Thermal performance of hybrid-inspired coolant for radiator application - Benedict, F.; Kumar, Amit; K., Kadirgama; Mohammed, Hussein A.; D., Ramasamy; Mahendran, Samykano; Saidur, R. (MDPI AG, 2020)
Due to the increasing demand in industrial application, nanofluids have attracted the considerable attention of researchers in recent decades. The addition of nanocellulose (CNC) with water (W) and ethylene glycol (EG) to a coolant for a radiator application exhibits beneficial properties to improve the efficiency of the radiator. The focus of the present work was to investigate the performance of mono or hybrid metal oxide such as Al2O3 and TiO2 with or without plant base-extracted CNC with varying concentrations as a better heat transfer nanofluid in comparison to distilled water as a radiator coolant. The CNC is dispersed in the base fluid of EG and W with a 60:40 ratio. The highest absorption peak was noticed at 0.9% volume concentration of TiO2, Al2O3, CNC, Al2O3/TiO2, and Al2O3/CNC nanofluids which indicates a better stability of the nanofluids’ suspension. Better thermal conductivity improvement was observed for the Al2O3 nanofluids in all mono nanofluids followed by the CNC and TiO2 nanofluids, respectively. The thermal conductivity of the Al2O3/CNC hybrid nanofluids with 0.9% volume concentration was found to be superior than that of the Al2O3/TiO2 hybrid nanofluids. Al2O3/CNC hybrid nanofluid dominates over other mono and hybrid nanofluids in terms of viscosity at all volume concentrations. CNC nanofluids (all volume concentrations) exhibited the highest specific heat capacity than other mono nanofluids. Additionally, in both hybrid nanofluids, Al2O3/CNC showed the lowest specific heat capacity. The optimized volume concentration from the statistical analytical tool was found to be 0.5%. The experimental results show that the heat transfer coefficient, convective heat transfer, Reynolds number and the Nusselt number have a proportional relationship with the volumetric flow rate. Hybrid nanofluids exhibit better thermal conductivity than mono nanofluids. For instance, a better thermal conductivity improvement was shown by the mono Al2O3 nanofluids than the CNC and TiO2 nanofluids. On the other hand, superior thermal conductivity was observed for the Al2O3/CNC hybrid nanofluids compared to the other mono and hybrid ones (Al2O3/TiO2).